Iron-folic acid adherence and associated factors among pregnant women attending antenatal care at Metema District, Northwest Ethiopia - Yismaw, Ayenew Engida; Tulu, Helen Bekele; Kassie, Fisseha Yetwale; Araya, Bilen Mekonnen (Frontiers in Public Health, 2022)
Background Iron deficiency accounts for about half of anemia cases worldwide. Iron and folate supplementation can effectively control and prevent anemia during pregnancy. Despite the efforts to reduce iron deficiency anemia during pregnancy, only a few women took an iron supplement as recommended. The aim of this study is to assess adherence to iron-folic acid supplementation and associated factors. Methods A facility-based cross-sectional study was conducted from April 1 to May 31, 2021, among pregnant women attending the antenatal care clinic at Metema district governmental health institutions. Data was collected through face-to-face interviews with an interviewer-administered questionnaire. Epi info version 7.1 and SPSS 20 were used for data entry and analysis. Binary logistic regression analysis was done to identify factors associated with iron-folic acid supplementation for pregnant women. Significant associations were determined based on the adjusted odds ratio (AOR) and 95% confidence, with a p-value < 0.05. Results The proportion of pregnant women adhering to iron-folic acid supplementation was 34.9% (95% CI: 31, 38.8%). Maternal educational status [AOR = 6.09, 95% CI (3.26, 11.4)], time of first antenatal consultation [AOR = 1.95, 95% CI (1.25, 3.06)], having good knowledge of iron with folic acid supplementation [AOR = 2.80, 95% CI (1.83, 4.28)], having a good understanding of anemia [AOR = 1.61, 95% CI (1.06, 2.43)], and a history of anemia during current pregnancy [AOR = 2.31, 95% CI (1.36, 3.94)] were factors affecting iron-folic acid supplementation adherence. Conclusions Iron-folic acid supplementation adherence was low in the study area. Increasing maternal awareness, having good knowledge about the benefits of iron-folate supplements, and early registration to antenatal care were positive determinants of iron with folic acid adherence.